Investigation of sub-wet bulb temperature evaporative cooling system for cooling in buildings - Alharbi, Abdulrahman (2014)
The work presented in this thesis investigates design, computer modelling and testing a sub-wet bulb temperature evaporative cooling system for space air conditioning in buildings. The context of this evaporative cooling technology design is specifically targeted at locations with a hot and dry climate such as that prevailing in most regions of Middle East countries. The focus of this technology is to address the ever-escalating energy consumption in buildings for space cooling using mechanical vapour compression air conditioning systems. In this work, two evaporative cooling configurations both based on sub-wet bulb temperature principle have been studied. Furthermore, in these designs, it was sought to adopt porous ceramic materials as wet media for the evaporative cooler and as building element and use of heat pipes as heat transfer devices. In the first test rig, the prototype system uses porous ceramic materials as part of a functioning building wall element. Experimental and modelling results were obtained for ambient inlet air dry bulb temperature of 30 and 35oC, relative humidity ranging from 35% to 55% and intake air velocity less than 2 (m/s). It was found that the design achieved sub-wet bulb air temperature conditions and a maximum cooling capacity approaching 242 W/m2 of exposed ceramic material wet surface area. The wet bulb effectiveness of the system was higher than unity. The second design exploits the high thermal conductivity of heat pipes to be integrated as an effective heat transfer device with wet porous ceramic flat panels for evaporative cooling. The thermal performance of the prototype was presented and the computer model was validated using laboratory tests at temperatures of 30 and 35oC and relative humidity ranging from 35% to 55%. It was found that at airflow rates of 0.0031kg/s, inlet dry-bulb temperature of 35oC and relative humidity of 35%, the supply air could be cooled to below the inlet air wet bulb temperature and achieve a maximum cooling capacity of about 206 W/m2 of wet ceramic surface area.